2021
DOI: 10.33223/epj/133474
|View full text |Cite
|
Sign up to set email alerts
|

Land suitability analysis for solar farms exploitation using the GIS and Analytic Hierarchy Process (AHP) – a case study of Morocco

Abstract: Given Morocco's geographical position and climatic conditions, solar energy will supply a large portion of the country's energy demand. In this paper, the suitability of Moroccan lands for hosting Solar Power Plants was studied using the combination of the Geographic Information System (GIS) and the Analytical Hierarchy Method (AHP). The multi-criteria decision framework integrates technical, socio-economic and environmental constraints. For this purpose, a GIS database was created using layers from various so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Integrating GIS-based and MCDM techniques has become instrumental in spatial analyses, particularly in risk and suitability assessments for renewable energy projects like solar and wind. Numerous MCDM methods, including AHP [8,9,11,15,28,49,[57][58][59], fuzzy AHP [16,47,60], integrated AHP [36], analytical network process (ANP) [18], decision-making trial and evaluation laboratory (DEMATEL) [18], adaptive neuro-fuzzy inference system (ANFIS) [19], density-based clustering [29], best-worst method (BMW) [1], weighted linear combination (WLC) [1,5,8,47,49], data envelopment analysis (DEA) [61], fuzzy complex proportional assessment (COPRAS) [61], preference ranking organization method for enrichment evaluations (PROMETHEE II) [15], and spatial decision support system (SDSS) [4], have been applied in wind power resource assessments. Among these, AHP stands out as a robust and widely utilized technique due to its simplicity and effectiveness in solving complex decision problems within specific case studies.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating GIS-based and MCDM techniques has become instrumental in spatial analyses, particularly in risk and suitability assessments for renewable energy projects like solar and wind. Numerous MCDM methods, including AHP [8,9,11,15,28,49,[57][58][59], fuzzy AHP [16,47,60], integrated AHP [36], analytical network process (ANP) [18], decision-making trial and evaluation laboratory (DEMATEL) [18], adaptive neuro-fuzzy inference system (ANFIS) [19], density-based clustering [29], best-worst method (BMW) [1], weighted linear combination (WLC) [1,5,8,47,49], data envelopment analysis (DEA) [61], fuzzy complex proportional assessment (COPRAS) [61], preference ranking organization method for enrichment evaluations (PROMETHEE II) [15], and spatial decision support system (SDSS) [4], have been applied in wind power resource assessments. Among these, AHP stands out as a robust and widely utilized technique due to its simplicity and effectiveness in solving complex decision problems within specific case studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there is potential for variations in national regulations concerning the categorization of settlements (urban versus rural) [80] and limitations on construction within risk areas. Studies should also incorporate additional criteria and parameters, such as wind speed [78], average annual precipitation [81], distance to wildlife [23,82], distance from the airport [28], aspect [83], land surface temperature [4], as well as other relevant factors based on the specific site's applicability. Furthermore, alternative methodologies have been developed when considering prioritizing factors.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the pertinent parameters for installing solar power plants and assessing their relative significance, GIS technology can accurately identify optimal areas for efficient and cost-effective energy production [2]. It enables the analysis and visualization of spatial data, allowing users to assess various factors and criteria to identify suitable locations for specific purposes, such as site selection for different projects or initiatives [1, [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-Criteria Decision-Making (MCDM) methods provide a structured and systematic approach to handle conflicting criteria and make informed decisions. The literature review identified 33 [2,4,[7][8][9][10][11][12][13][14][15].…”
Section: Multi-criteria Decision-making Methodsmentioning
confidence: 99%
“…Greece AHP, TOPSIS [11] Khuzestan AHP, fuzzy Boolean logic [27] Turkey AHP [22,24,[28][29][30][31][32] Morocco AHP [33][34][35] China AHP [36] Israel AHP [37] Algeria AHP, EQual Weighted (EQW), Best Worst Method (BWM) [15,[38][39][40] Peru AHP [41] Afghanistan AHP, ANP [42] Iraq AHP, Boolean AHP [8,43] Iran AHP, fuzzy logic, weighted linear Combination (WLC) [44] Thailand AHP [45] Ethiopia AHP [46] Egypt AHP [47] Ireland AHP [48] Chile AHP, ordered weighted averaging [10] Philippines AHP [25] Tanzania AHP [49] Saudi Arabia AHP [23] T A B L E 3 Summary of studies on EVCS site selection using GIS and AHP.…”
Section: Study Area Methods Referencesmentioning
confidence: 99%